2021
DOI: 10.1101/2021.05.05.442736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer mutational processes vary in their association with replication timing and chromatin accessibility

Abstract: BackgroundCancer somatic mutations are the product of multiple mutational and repair processes, which are tightly associated with DNA replication. Distinctive patterns of somatic mutations accumulation in tumors, termed mutational signatures, are indicative of processes the tumors underwent. While tumor mutational load is correlated with late replicating regions and spatial genome organization, much is unknown about the association of many different mutational processes and replication timing, and the interpla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…To prevent signature overfitting, we selected a subset of signatures for each cell type based on biologically expected mutational pathways. In CLL, SBS 1, 5, 9 and 40 are established as the predominant mutational signatures 1,28,33,45 . SBS 1, 5, and 40, are clock-like signatures – highly ubiquitous signatures of unknown etiology that increase in abundance with age 1,46 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To prevent signature overfitting, we selected a subset of signatures for each cell type based on biologically expected mutational pathways. In CLL, SBS 1, 5, 9 and 40 are established as the predominant mutational signatures 1,28,33,45 . SBS 1, 5, and 40, are clock-like signatures – highly ubiquitous signatures of unknown etiology that increase in abundance with age 1,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Some mutational processes are shared (e.g., those manifesting as single base substitution (SBS) signatures 1, 5, and 40), and others are more specific to subsets of cell or cancer types (e.g., MMR deficiency). Previous studies showed that different mutational processes – and their resulting mutational signatures – have differential relationships to replication timing 10,12,15,27,28 . For example, SBS signatures 1, 8, 9, and 17 were shown to be enriched in late replicating regions of the genome, while SBS 5, 21, 40, and 44 showed either bias to early replication or no bias at all.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations